Ответы и объяснения

Лучший Ответ!
2013-03-21T21:03:57+00:00

Я на 100% не уверена, но, кажется, так:

1) \frac{sin^{2}\alpha - 1}{1-cos^{2}\alpha}=\frac{sin^{2}\alpha - sin^{2}\alpha-cos^{2}\alpha}{sin^{2}\alpha+cos^{2}\alpha-cos^{2}\alpha}=-ctg^{2}\alpha

2) \frac{1}{1+cos\alpha}+\frac{1}{1-cos\alpha}=\frac{1}{1-cos^{2}\alpha}=\frac{1}{sin^{2}\alpha+cos^{2}\alpha-cos^{2}\alpha}=\frac{1}{sin^{2}\alpha}=ctg^{2}\alpha+1

3)\frac{ctgxsinx}{1+tg^{2}x}=\frac{\frac{cosx}{sinx}}{\frac{1}{cos^{2}x}}=\frac{cosx}{\frac{1}{cos^{2}x}}=cos^{3}x